Residual Neuromuscular Block in the Elderly: Incidence and Clinical Implications. (December 2015) - Murphy, Glenn S.; Szokol, Joseph W.; Avram, Michael J.; Greenberg, Steven B.; Shear, Torin D.; Vender, Jeffery S.; Parikh, Kruti N.; Patel, Shivani S.; Patel, Aashka
Abstract : Background: Elderly patients are at increased risk for anesthesia-related complications. Postoperative residual neuromuscular block (PRNB) in the elderly, defined as a train-of-four ratio less than 0.9, may exacerbate preexisting muscle weakness and respiratory dysfunction. In this investigation, the incidence of PRNB and associated adverse events were assessed in an elderly (70 to 90 yr) and younger cohort (18 to 50 yr). Methods: Data were prospectively collected on 150 younger and 150 elderly patients. Train-of-four ratios were measured on arrival to the postanesthesia care unit (PACU). After tracheal extubation, patients were examined for adverse respiratory events during transport to the PACU, for 30 min after PACU admission, and during hospital admission. Postoperative muscle weakness was quantified using a standardized examination, and PACU and hospital lengths of stay were determined. Results: The incidence of PRNB was 57.7% in elderly and 30.0% in younger patients (difference, −27.7%; 99% CI, −41.2 to −13.1%; P < 0.001). Airway obstruction, hypoxemic events, signs and symptoms of muscle weakness, postoperative pulmonary complications, and increased PACU and hospital lengths of stay were observed more frequently in the elderly (all P < 0.01). Within each cohort, most adverse events were observed in patients with PRNB. Younger patients with PRNB received larger total doses of rocuronium than did those without it (60 vs. 50 mg, P < 0.01), but there were no differences in rocuronium dose between elderly patients with PRNB and those without it (both 50 mg). Conclusion: The elderly are at increased risk for PRNB and associated adverse outcomes. Abstract : In a prospective study of 150 elderly and 150 younger patients, the incidence of postoperative residual neuromuscular block was high in both groups, but higher in the elderly (58% compared with 30%), associated with more frequent hypoxemia, postoperative pulmonary complications, and longer hospital length of stay in the elderly.